Enhancing resilience to climate change: a comprehensive PRISMA review of agricultural and non-agricultural adaptation strategies for Ghana - Silas Uwumborge Takal; Abdul-Wahab Tahiru; IM Rizwanul Fattah; Samuel Jerry Cobbina; Wilhemina Asare; Samuel Kojo Abanyie (Cogent Social Sciences)
Farming in Ghana is highly vulnerable to climate change due to factors such as limited financial resources, inadequate land availability, lack of access to technology, and insufficient public infrastructure, including roads, weather forecasting systems, and extension services. Adaptation serves as a critical first line of defense, reducing the impact of climate‑induced challenges in agriculture. This study examines how Ghanaian farmers have adapted their practices to cope with environmental changes and the resulting implications for agricultural resilience. The research analyzed existing knowledge and practices related to climate adaptation in agriculture, reviewing 20 relevant publications identified through ProQuest and Web of Science databases, guided by PRISMA Statement protocols. Key adaptation strategies included crop diversification, use of drought‑resistant varieties, adjustments to planting schedules, soil moisture conservation through appropriate tillage techniques, improved irrigation efficiency, and agroforestry. These practices highlight the resourcefulness of farmers in mitigating climate impacts. Findings emphasize the critical role of educational initiatives, outreach programs, and extension services in supporting farmers’ adaptive capacities. By fostering awareness and knowledge sharing across all age groups, these measures can strengthen agricultural resilience and enhance the sustainability of farming practices in the context of a changing climate.